2012
DOI: 10.1016/j.shpsc.2012.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Two types of typicality: Rethinking the role of statistical typicality in ordinary causal attributions

Abstract: Recent work on the role of norms in the use of causal language by ordinary people has led to a consensus among several researchers: The consensus position is that causal attributions are sensitive to both statistical norms and prescriptive norms. But what is a statistical norm? We argue that there are at least two types that should be distinguished-agent-level statistical norms and population-level statistical norms. We then suggest an alternative account of ordinary causal attributions about agents (the respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
88
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(97 citation statements)
references
References 4 publications
4
88
0
Order By: Relevance
“…Particularly in the case of prescriptive norms, there are several explanations for this effect. This effect is predicted by our model, but it is also predicted by a wide variety of other views which invoke everything from conversational pragmatics to motivational bias (Alicke et al, 2011;Driver, 2008;Strevens, 2013;Sytsma et al, 2012), in addition to being predicted by one of the measures discussed above (namely SP ). However, our model predicts a further effect, for both prescriptive and statistical norms.…”
Section: Abnormal Deflationsupporting
confidence: 64%
See 1 more Smart Citation
“…Particularly in the case of prescriptive norms, there are several explanations for this effect. This effect is predicted by our model, but it is also predicted by a wide variety of other views which invoke everything from conversational pragmatics to motivational bias (Alicke et al, 2011;Driver, 2008;Strevens, 2013;Sytsma et al, 2012), in addition to being predicted by one of the measures discussed above (namely SP ). However, our model predicts a further effect, for both prescriptive and statistical norms.…”
Section: Abnormal Deflationsupporting
confidence: 64%
“…Researchers have suggested that the effect might arise as a result of conversational pragmatics (Driver, 2008), motivational bias (Alicke et al, 2011), relativity to frameworks (Strevens, 2013), responsibility attributions (Sytsma, Livengood, & Rose, 2012), or people's understanding of the question . Here, we will be exploring a general approach that has been defended by a number of researchers in recent years, namely, that abnormal inflation reflects a process in which certain counterfactuals are treated as in some way more relevant than others (Blanchard & Schaffer, 2016;Halpern & Hitchcock, 2015;Knobe, 2010;Phillips et al, 2015).…”
Section: First Effect: Abnormal Inflationmentioning
confidence: 99%
“…In the previous section, however, we saw that statistical norms did not have a notable impact on folk causal attributions for the Lauren alone case. And this finding is in keeping with the results reported in Sytsma, Livengood, and Rose (2012 (2012) for discussion. That said, one might think that there is good reason to believe that statistical norms play an independent role in some folk causal attributions.…”
Section: Revising the Dtn Accountssupporting
confidence: 93%
“…Hitchcock's theory fails to satisfy the FAD for the original Lauren and Jane case at least in part because the rules of thumb for assigning default and deviant values say nothing about prescriptive norms. Many studies have shown that ordinary causal attributions are sensitive to such norms (e.g., Alicke, 1992;Hitchcock and Knobe, 2009;Alicke et al, 2011;Sytsma, Livengood, and Rose, 2012). Since the Lauren and Jane case includes information about prescriptive norms, it is not completely surprising that Hitchcock's theory fails to satisfy the FAD with respect to it.…”
Section: Solution 1: Focus On Permissibilitymentioning
confidence: 99%
See 1 more Smart Citation